Formaldehyde induces ferroptosis in hippocampal neuronal cells by upregulation of the Warburg effect. (30th January 2021) - Li, Xiao-Na; Yang, San-Qiao; Li, Min; Li, Xue-Song; Tian, Qing; Xiao, Fan; Tang, Yi-Yun; Kang, Xuan; Wang, Chun-Yan; Zou, Wei; Zhang, Ping; Tang, Xiao-Qing
Abstract: The mechanisms underlying formaldehyde (FA)-induced neurotoxicity have not yet been fully clarified. Ferroptosis is a novel regulatory cell death and the Warburg effect is involved in regulating neural function. In this study, we investigated whether FA-induced neurotoxicity is implicated in neuronal ferroptosis and determined whether the Warburg effect mediates FA-induced neuronal ferroptosis. We found that FA (0.1, 0.5 and 1.0 mM, 6 h) induced cell death in HT22 cells (a cell line of mouse hippocampal neuron), as evidenced by a decrease in cell viability and an increase in cell mortality; enhanced oxidative stress, as evidenced by a decrease in glutathione (GSH) and increases in malondialdehyde (MDA), 4-Hydroxynonenal (4-HNE), as well as reactive oxygen species (ROS); increased the iron content; and upregulated the ferroptosis-associated genes, including Ptgs2 (prostaglandin-endoperoxide synthase 2), GLS2 (glutaminase 2), solute carrier family 1 member 5 (SLC1A5), and solute carrier family 38 member 1 (SLC38A1) in HT22 cells, indicating the inductive role of FA in the ferroptosis of HT22 cells. Meanwhile, we found that FA (0.1, 1, 10 μmol) decreased the cross-sectional of mitochondria, increased the level of lipid ROS and iron content in primary hippocampal cells. We showed that FA (0.1, 0.5 and 1.0 mM, 6 h) upregulated the Warburg effect in HT22 cells, as evidenced by up-regulations of pyruvate kinase M2 (PKM2), pyruvate dehydrogenase kinase 1(PDK-1), and lactate dehydrogenase (LDHA) proteins; down-regulation of pyruvate dehydrogenase (PDH); and an increase in lactate production. Also, we found that FA (0.1, 1, 10 μmol, 7 d) upregulated the Warburg effect in hippocampal tissue, as evidenced by up-regulations of PKM2, PDK-1, and LDHA proteins; down-regulation of PDH. Furthermore, the inhibition of the Warburg effect by dichloroacetate (DCA) protected HT22 cells against FA-induced ferroptosis and cell death. Collectively, these data indicated that FA induces ferroptosis in hippocampal neuronal cells by upregulation of the Warburg effect.